Doctor Apolinary Tarnawski (1851-1943) - the pioneer of natural medicine and physiotherapy in geriatrics in Poland : Doktor Apolinary Tarnawski (1851. - 1943.) - pionir prirodne medicine i fizioterapije gerijatrijskih pacijenata u Poljskoj - Migała, Mariusz (Array, 2021)
Doctor Apolinary Tarnawski (1851–1943) was undoubtedly the precursor of modern natural medicine, preventive medicine, and geriatric physiotherapy in Poland. Based on the experience gained from foreign scientific travel, own knowledge and experience, he developed an original method that he successfully used in his own clinic in Kosów. His assumptions proved to be timeless, and despite the passage of many years have not lost their relevance.